Rekonstruksi Sejarah Lokal Perang Panta - Yusra Dewi; Agus Salim (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2022)
Abstract: Historical reconstruction must be done because history is not necessarily known to many people. With the reconstruction process, it is hoped that history can serve as an educational, inspirational, instructive, and recreational function for the readers. Therefore, the purpose of this study is to reconstruct the local history of the